“La notte e l’aurora”. Padre Balducci e Giorgio La Pira: un dialogo educativo rivolto al futuro - Certini, Rossella (Studi sulla Formazione/Open Journal of Education, 2024)
This paper briefly addresses the relationship of knowledge and esteem between Giorgio La Pira and Father Ernesto Balducci. The classic themes of Lapirian thought are addressed - universal peace, intercultural dialogue, social justice - in particular through the rereading of the biography that Balducci dedicated to the mayor of Florence in 1986. There are three central points of the comparison between the two religious figures: Florence seen like Polis; universal civilization and plurality of cultures; the Mediterranean talks. In their mutual closeness and knowledge, Balducci and La Pira remained faithful to their respective cultural and political positions: the former more critical and philosophical-pedagogical, the latter more historical and empirical. Together with other important religious people from the Florentine area, they gave life to an extraordinary cultural season which affected the city of Florence starting after the Second World War and which still today constitutes an exquisitely critical and profoundly divergent model of meeting and dialogue.